PELATIHAN PENYUSUNAN LAPORAN LABA/RUGI DI PANTI ASUHAN ASIH LESTARI - Dermawan, Elizabeth Sugiarto; Pratama, Go Cecilia Claudia Pratama; Agusnia, Windy; Daniswara, Frederick (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The topic of this PKM is Preparing a Profit/Loss Report, which is felt necessary by the students of the Asih Lestari Orphanage and this PKM was held on the basis of invitation no.039/YPA.AL/SK/VIII/2024 from the management of the Asih Lestari Orphanage (AL). Preparing a profit/loss report containing profit/loss information for a certain period can be a reference for viewing the entity's business development. Providing an understanding of preparing profit/loss reports needs to be given considering that these orphanage students will live independently after high school. The topics that will be discussed in this PKM are related to the preparation of profit/loss reports for service companies (single step), profit/loss reports for trading companies (multiple step), and profit/loss reports for manufacturing companies (multiple step). This PKM is expected not only to prepare reports when the Asih Lestari orphanage students start independent businesses, but also to support learning at school. This PKM was implemented on Monday 16 September 2024 pk. 08.30-13.00, with tutorials, exercises and evaluation through quizzes and questionnaires. This mandatory PKM output is presented in SENAPENMAS, while additional output will be the creation of HKI for the training module for preparing profit/loss reports. Exercises are carried out in each session to evaluate students' understanding of the material presented. At the end of the session, a questionnaire was created to evaluate the implementation of this PKM, the results of which showed that there was an increase in understanding of preparing profit/loss reports before and after the training. ABSTRAKTopik PKM ini adalah Penyusunan Laporan Laba / Rugi, yang dirasakan perlu oleh siswa siswi panti asuhan Asih Lestari dan PKM ini terselenggara atas dasar undangan no.039/YPA.AL/SK/VIII/2024 dari pengelola Panti Asuhan Asih Lestari (AL). Penyusunan laporan laba / rugi memuat informasi laba / rugi periode tertentu dapat menjadi acuan untuk melihat perkembangan usaha entitas. Pembekalan pemahaman penyusunan laporan laba/rugi perlu diberikan mengingat siswa-siswi panti asuhan ini akan hidup mandiri selepas SMA. Topik yang akan dibahas dalam PKM ini terkait penyusunan laporan laba/rugi bagi perusahaan jasa (single step), laporan laba / rugi perusahaan dagang (multiple step), dan laporan laba / rugi perusahaan manufaktur (multiple step). PKM ini diharapkan selain untuk mempersiapkan penyusunan laporan saat siswa / siswi panti asuhan Asih Lestari merintis usaha mandiri, juga untuk menunjang pembelajaran di sekolah. PKM ini telah dilaksanakan pada hari Senin tanggal 16 September 2024 pk. 08.30-13.00, dengan cara tutorial, latihan, dan evaluasi melalui kuis serta angket. Luaran wajib PKM ini disajikan dalam SENAPENMAS, sedangkan luaran tambahan akan dibuatkan HKI atas modul pelatihan penyusunan laporan laba/rugi. Latihan dilakukan di setiap sessi untuk evaluasi pemahaman siswa terhadap materi yang disampaikan. Di akhir sessi dibuat angket untuk evaluasi pelaksanaan PKM ini yang hasilnya menunjukkan ada peningkatan pemahaman penyusunan laporan laba/rugi sebelum dan setelah pelatihan.